The Effectiveness of a STEAM-Integrated Project-Based Learning Model for Teaching Motorcycle CVT Diagnostics in Vocational Schools - Adek Irawan; Nurliana Nasution; Rizki Novendra; Yogo Turnandes; Budi Cahya; Nurli Indra Sari (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study examines the effectiveness of integrating Project-Based Learning (PBL) with a STEAM approach to enhance students’ conceptual understanding and diagnostic skills in continuous variable transmission (CVT) systems within vocational education. A quasi-experimental design was employed involving 34 Grade XII students from the Motorcycle Engineering program at SMK Negeri 4 Rambah, Indonesia. Participants were divided into an experimental group receiving PBL-STEAM instruction and a control group receiving traditional teaching. Data were collected through posttests and analyzed using N-gain, independent samples t-tests, and effect size (Cohen’s d). The experimental group achieved a higher mean posttest score in conceptual understanding (84.24) compared to the control group (74.00). The N-gain for the experimental group was 0.68 (high), while the control group showed 0.28 (low). Diagnostic skills also improved significantly, with mean scores of 90.00 (experimental) and 76.00 (control). Statistical analysis revealed significant differences between groups (p 0.05). Effect sizes were large (d = 1.77 for conceptual understanding; d = 2.68 for diagnostic skills). The findings indicate that the PBL-STEAM approach substantially improves both conceptual mastery and diagnostic skills. This model aligns well with vocational education objectives and supports the development of competencies relevant to industry demands.